High-temperature-resistant connection adhesive tape and production process thereof

By using composite silica and zirconium oxide fillers in the coupling tape and hydrophobic modification of the silica surface, the problem of reducing the adhesive ability of the tape in a high humidity environment is solved, and good high temperature resistance and waterproofing performance are achieved.

CN119552590APending Publication Date: 2025-03-04ANHUI BAOLIYUAN NEW MATERIALS CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411777716.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-05
Publication Date
2025-03-04

AI Technical Summary

Technical Problem

When using silicone adhesive in a high humidity environment, the adhesive forms hydrogen bonds with water, reducing the adhesive ability and high temperature resistance.

Method used

By uniformly combining the heat-resistant filler silica with zirconia and hydrophobic modification on the surface of the silica, the high temperature resistance and waterproof properties of the organic silicone adhesive are improved.

Benefits of technology

It achieves good high-temperature resistance and adhesive properties under high humidity environments, and improves the temperature and humidity resistance of the tape.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention discloses a high-temperature-resistant connection adhesive tape and a production process thereof, the high-temperature-resistant connection adhesive tape sequentially comprises a polyimide film, an adhesive layer and a release film from top to bottom, the adhesive layer is obtained by coating a waterproof and high-temperature-resistant organic silicon adhesive, and the waterproof and high-temperature-resistant organic silicon adhesive comprises, by mass, 5-10 parts of a curing agent, 1-5 parts of a curing agent and 1- comprising the following components in parts by mass: 200 to 250 parts of polydimethylsiloxane, 0.05 to 0.1 part of a platinum catalyst, 0.005 to 0.01 part of an inhibitor, 10 to 20 parts of a hydrophobic coated zirconium oxide carrier and 5 to 10 parts of a cross-linking agent, according to the high-temperature-resistant connection adhesive tape disclosed by the invention, the adhesive layer is subjected to hydrophobic high-temperature-resistant modification, so that the high-temperature-resistant connection adhesive tape disclosed by the invention can maintain good high-temperature resistance in a high-humidity environment; the filler can improve the high-temperature resistance of the adhesive and has certain waterproof capacity, and the obtained high-temperature-resistant connection adhesive tape is good in adhesive performance and high in temperature and humidity resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of splicing tapes, and in particular relates to a high temperature resistant splicing tape and a production process thereof. Background Art

[0002] Splicing tape is a type of tape that can connect two objects together. It has good adhesion properties, can effectively fix the connection, and can withstand tensile and shear forces. It has a wide range of applications. The main application industries are currently medical, industrial, mechanical production, logistics, and automotive. During mechanical production and processing, the splicing tape will have its adhesion reduced due to the high temperature generated during processing, and the tape will be severely deformed and break. Silicone adhesives have good high temperature resistance, but silicone adhesives are easily weakened by the hydrogen bonds formed on the surface of water and silicone adhesives in a humid environment.

[0003] Patent CN117004336A discloses a high temperature resistant tape, which uses a methacrylate-butadiene-styrene copolymer modified resin as a base material to improve the impact resistance of the tape, and uses a high temperature resistant acrylate to improve the high temperature resistance of the tape. However, the acrylate has insufficient moisture resistance, and the bonding performance decreases rapidly in a high temperature and high humidity environment, and cannot be used for high-strength bonding requirements.

[0004] Patent CN116120848A discloses a modified acrylic tape, which improves the high temperature resistance and impact resistance of the tape by arranging a fiber layer made of glass fiber, and bonds two fiber layers with an organic silicone adhesive, using a two-component acrylic copolymer resin material as an adhesive layer; however, the silicone layer used between the fiber layers in this solution will weaken the bonding ability in a humid environment, resulting in possible displacement between the tape layers, resulting in a decrease in the high temperature resistance of the tape. Summary of the invention

[0005] The purpose of the present invention is to solve the problem that the use of organic silicone adhesive as an adhesive layer of a splicing tape in a high humidity environment will cause the organic silicone adhesive to form hydrogen bonds with water, thereby reducing the bonding ability, and the high temperature resistant filler reacts with water to reduce the high temperature resistance of the splicing tape, and to provide a high temperature resistant splicing tape and a production process thereof.

[0006] The present invention uniformly compounds heat-resistant filler silica with zirconium oxide having improved heat resistance, and at the same time attaches zinc oxide to the surface of zirconium oxide, utilizes the heat resistance of silica and zirconium oxide and the ability of zinc oxide to promote the degree of curing to improve the high-temperature resistance of the organic silicone adhesive, and improves the hydrophobicity of silica by hydrophobic modification of the silica surface, thereby improving the moisture resistance of the organic silicone adhesive, and obtaining a moisture-resistant and high-temperature resistant splicing tape.

[0007] The purpose of the present invention can be achieved by the following technical solutions: A high temperature resistant splicing tape comprises, from top to bottom, a polyimide film, an adhesive layer and a release film, wherein the adhesive layer is coated with a waterproof and high temperature resistant organic silicone adhesive, and the waterproof and high temperature resistant organic silicone adhesive comprises the following components in parts by mass: 200-250 parts of polydimethylsiloxane, 0.05-0.1 parts of platinum catalyst, 0.005-0.01 parts of inhibitor, 10-20 parts of hydrophobically coated zirconium oxide carrier and 5-10 parts of cross-linking agent; The inhibitor is 1-ethynyl-1-cyclohexanol; The crosslinking agent is a dimethylsiloxane copolymer terminated with methylhydrogensiloxane; Platinum catalysts include, but are not limited to, chloroplatinic acid / olefin complexes, chloroplatinic acid / olefin siloxane complexes, and chloroplatinic acid / divinyltetramethyldisiloxane complexes.

[0008] A production process of a high temperature resistant splicing tape comprises the following steps: Step 1: Use a planetary mixer to homogenize and mix the platinum catalyst and the inhibitor with 30 times their mass of polydimethylsiloxane at a rotation speed of 1500-1800rpm for 3-5min to obtain a platinum catalyst dilution and an inhibitor dilution. Use a planetary mixer to homogenize and mix the remaining polydimethylsiloxane and the catalyst solution with the platinum catalyst solution and the inhibitor solution successively, with each mixing time of 3-5min. Then, add the hydrophobic coated zirconia carrier three times, with each mixing time of 1-2min. Finally, add the cross-linking agent and mix for 1-2min to obtain a waterproof and high temperature resistant organic silicone adhesive.

[0009] Step 2: Apply waterproof and high temperature resistant organic silicone adhesive on one side of the polyimide film to obtain an adhesive layer, the adhesive layer coating thickness is 40-50 μm, the thickness of the polyimide film is 25-35 μm, and a release film is attached to the lower surface of the adhesive layer. The release film is a fluoroplastic release film with a thickness of 50-75 μm to obtain a high temperature resistant splicing tape.

[0010] Further, the hydrophobic coated zirconia carrier is prepared by the following steps: In a reaction kettle, the coated zirconia carrier is dispersed in anhydrous ethanol, 60wt% ammonia water is added and stirred vigorously for 30-50min, then dodecyltriethoxysilane is added to the reaction kettle, the temperature is raised to 70-80°C and the reaction is carried out for 6-7h, the precipitate is washed after centrifugation, and vacuum dried to obtain a hydrophobic coated zirconia carrier.

[0011] Furthermore, the usage ratio of the coated zirconium oxide carrier, anhydrous ethanol, ammonia water and dodecyltriethoxysilane is 15-20 g: 100-150 mL: 30-50 mL: 3-4 g.

[0012] Further, the coated zirconia carrier is prepared by the following steps: In a reaction kettle, the zinc oxide / zirconium-based carrier is ultrasonically dispersed in a 90wt% ethanol solution, ammonia water is added, and then tetraethoxysilane is added and stirred for reaction for 1-2 hours. The precipitate is washed after centrifugation, vacuum dried, and transferred to a muffle furnace and heated to 400-450°C and calcined for 3-4 hours by passing oxygen to obtain a coated zirconium oxide carrier.

[0013] Furthermore, the usage ratio of zinc oxide / zirconium-based carrier, ethanol solution, ammonia water and tetraethoxysilane is 15-20 g: 500-600 mL: 20-30 mL: 2-3 mL.

[0014] Further, the zinc oxide / zirconium-based carrier is prepared by the following steps: The modified zirconium-based carrier is dispersed in a 5wt% zinc nitrate methanol solution in a reactor and stirred for 24-36 hours. Then, deionized water and hexamethylenetetramine are added to the reactor, stirred evenly, heated to 120-130°C and reacted for 6-8 hours. After cooling, the precipitate is washed by centrifugation and vacuum dried to obtain a zinc oxide / zirconium-based carrier.

[0015] Furthermore, the usage ratio of the modified zirconium-based carrier, the zinc nitrate methanol solution, the deionized water and the hexamethylenetetramine is 15-20 g: 200-300 mL: 20-30 mL: 10-15 g.

[0016] Further, the modified zirconium-based carrier is prepared by the following steps: S1. In a reaction kettle, zirconium oxychloride octahydrate and 2-aminoterephthalic acid are ultrasonically dispersed in a mixed solution of formic acid and N,N-dimethylformamide in equal volumes, the temperature is raised to 100-130° C. and the mixture is reacted for 40-48 hours. After cooling, the mixture is centrifuged, the precipitate is washed, and vacuum dried to obtain a zirconium-based carrier.

[0017] S2. In a reactor, heat and stir L-histidine in deionized water to dissolve the L-histidine, add the zirconium-based carrier activated at 120-130°C for 2-3 hours into the reactor, heat the reactor to 80-90°C for 10-12 hours, cool and centrifuge, wash the precipitate, and vacuum dry to obtain a modified zirconium-based carrier.

[0018] Furthermore, the dosage ratio of zirconium oxychloride octahydrate, 2-aminoterephthalic acid and the mixed solution in S1 is 25-30 g: 40-45 g: 800-1000 mL; the dosage ratio of L-histidine, deionized water and zirconium-based carrier in S2 is 10-20 g: 200-300 mL: 15-20 g.

[0019] Beneficial effects of the present invention: (1) The high temperature resistant splicing tape of the present invention improves the ability of the high temperature resistant splicing tape to maintain good high temperature resistance in a high humidity environment by modifying the adhesive layer to be hydrophobic and high temperature resistant. The filler in the waterproof and high temperature resistant organic silicone adhesive is modified so that the filler can have a certain waterproof ability while improving the high temperature resistance of the adhesive, thereby improving the temperature and humidity resistance of the adhesive layer. The obtained high temperature resistant splicing tape has good bonding performance and strong temperature and humidity resistance.

[0020] (2) The preparation method of the present invention uniformly compounds zirconium oxide and silicon dioxide to produce a synergistic effect, thereby improving the high temperature resistance of the waterproof and high temperature resistant organic silicone adhesive, and by hydrophobically modifying silicon dioxide, the hydrophobic properties of the waterproof and high temperature resistant organic silicone adhesive are improved while improving the high temperature resistance. The present invention grafts zinc ions onto a zirconium-based carrier via carboxyl groups, and then hydrothermally generates zinc oxide. The generated zinc oxide is uniformly combined with the zirconium-based carrier. The zirconium-based carrier is oxidized into zirconium oxide by calcination, while the degree of bonding between zinc oxide, zirconium oxide and silicon dioxide is enhanced. The obtained hydrophobic coated zirconium oxide carrier has a uniform degree of compounding, which has a good effect on improving the performance of the organic silicone adhesive. DETAILED DESCRIPTION

[0021] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0022] Embodiment 1: A high temperature resistant splicing tape, comprising, from top to bottom, a polyimide film, an adhesive layer and a release film, wherein the adhesive layer is coated with a waterproof and high temperature resistant organic silicone adhesive, and the waterproof and high temperature resistant organic silicone adhesive comprises the following components: 200 g polydimethylsiloxane, 0.05 g platinum catalyst, 0.005 g inhibitor, 10 g hydrophobically coated zirconium oxide carrier and 5 g cross-linking agent.

[0023] In this embodiment, the platinum catalyst is chloroplatinic acid / olefin complex.

[0024] A production process of a high temperature resistant splicing tape comprises the following steps: Step 1: In a reaction kettle, 25 g of zirconium oxychloride octahydrate and 40 g of 2-aminoterephthalic acid are ultrasonically dispersed in a mixed solution of equal volumes of 800 mL of formic acid and N,N-dimethylformamide, and the temperature is raised to 100°C for reaction for 40 hours. After cooling, the mixture is centrifuged at 7000 rpm for 3 minutes, and the precipitate is washed with N,N-dimethylformamide and ethanol respectively, and vacuum dried at 70°C for 10 hours to obtain a zirconium-based carrier.

[0025] Step 2: In a reactor, add 10 g of L-histidine to 200 mL of deionized water, heat and stir to dissolve the L-histidine, add 15 g of the zirconium-based carrier activated at 120°C for 2 hours to the reactor, heat the reactor to 80°C and react for 10 hours, centrifuge at 7000 rpm after cooling, wash the precipitate with deionized water, and vacuum dry at 70°C for 10 hours to obtain a modified zirconium-based carrier.

[0026] Step 3: In a reactor, disperse 15 g of the modified zirconium-based carrier in 200 mL of a 5 wt% zinc nitrate methanol solution and stir to react for 24 h. Then, add 20 mL of deionized water and 10 g of hexamethylenetetramine to the reactor, stir evenly, heat to 120 ° C, react for 6 h, cool, centrifuge at 7000 rpm to obtain a bottom precipitate, wash the precipitate with methanol, and vacuum dry at 70 ° C for 10 h to obtain a zinc oxide / zirconium-based carrier.

[0027] Step 4: In a reactor, ultrasonically disperse 15 g of zinc oxide / zirconium-based carrier in 500 mL of 90 wt% ethanol solution, add 20 mL of ammonia water, then add 2 mL of tetraethoxysilane and stir to react for 1 hour. After centrifugation at 7000 rpm, wash the precipitate with ethanol and deionized water, dry it in vacuo at 60 ° C for 20 hours, transfer it to a muffle furnace, pass oxygen, heat it to 400 ° C and calcine it for 3 hours to obtain a coated zirconium oxide carrier.

[0028] Step 5. Disperse 15 g of the coated zirconia carrier in 100 mL of anhydrous ethanol in a reactor, add 30 mL of 60 wt% ammonia water and stir vigorously for 30 min, then add 3 g of dodecyltriethoxysilane to the reactor, heat to 70 ° C and react for 6 h, wash the precipitate with anhydrous ethanol after centrifugation, and vacuum dry at 60 ° C for 12 h to obtain a hydrophobic coated zirconia carrier.

[0029] Step six: homogenize and mix the platinum catalyst and the inhibitor with 30 times their mass of polydimethylsiloxane respectively at a rotation speed of 1500 rpm using a planetary mixer, and mix each time for 3 minutes to obtain a platinum catalyst dilution and an inhibitor dilution. Use a planetary mixer to homogenize and mix the remaining polydimethylsiloxane and the catalyst solution with the platinum catalyst solution and the inhibitor solution successively for 3 minutes, and then add the hydrophobic coated zirconia carrier three times, each mixing time for 1 minute, and then add the methyl hydrogen siloxane-terminated dimethylsiloxane copolymer and mix for 1 minute to obtain a waterproof and high temperature resistant organic silicone adhesive.

[0030] Step seven: apply waterproof and high temperature resistant organic silicone adhesive on one side of the polyimide film to obtain an adhesive layer. The adhesive layer coating thickness is 40 μm, and the thickness of the polyimide film is 25 μm. A release film is attached to the lower surface of the adhesive layer. The release film is a fluoroplastic release film with a thickness of 50 μm to obtain a high temperature resistant splicing tape.

[0031] Embodiment 2: A high temperature resistant splicing tape, comprising, from top to bottom, a polyimide film, an adhesive layer and a release film, wherein the adhesive layer is coated with a waterproof and high temperature resistant organic silicone adhesive, and the waterproof and high temperature resistant organic silicone adhesive comprises the following components: 225 g polydimethylsiloxane, 0.075 g platinum catalyst, 0.075 g inhibitor, 15 g hydrophobically coated zirconium oxide support and 7.5 g cross-linking agent.

[0032] In this embodiment, the platinum catalyst is a chloroplatinic acid / olefin siloxane complex.

[0033] A production process of a high temperature resistant splicing tape comprises the following steps: Step 1: In a reaction kettle, 27.5 g zirconium oxychloride octahydrate and 42.5 g 2-aminoterephthalic acid were ultrasonically dispersed in a mixed solution of equal volumes of 900 mL formic acid and N, N-dimethylformamide, and the temperature was raised to 115°C for reaction for 44 h. After cooling, the mixture was centrifuged at 7500 rpm for 4 min. The precipitate was washed with N, N-dimethylformamide and ethanol respectively, and vacuum dried at 75°C for 11 h to obtain a zirconium-based carrier.

[0034] Step 2: In a reactor, add 15 g of L-histidine to 250 mL of deionized water, heat and stir to dissolve the L-histidine, add 17.5 g of the zirconium-based carrier activated at 125°C for 2.5 hours to the reactor, heat the reactor to 85°C and react for 11 hours, centrifuge at 7500 rpm after cooling, wash the precipitate with deionized water, and vacuum dry at 75°C for 11 hours to obtain a modified zirconium-based carrier.

[0035] Step 3: In a reactor, disperse 17.5 g of the modified zirconium-based carrier in 250 mL of a 5 wt% zinc nitrate methanol solution and stir to react for 30 h. Then, add 25 mL of deionized water and 12.5 g of hexamethylenetetramine to the reactor, stir evenly, heat to 125 ° C, and react for 7 h. After cooling, centrifuge at 7500 rpm to obtain a bottom precipitate. Wash the precipitate with methanol and vacuum dry it at 75 ° C for 11 h to obtain a zinc oxide / zirconium-based carrier.

[0036] Step 4: In a reactor, ultrasonically disperse 17.5 g of zinc oxide / zirconium-based carrier in 550 mL of 90 wt% ethanol solution, add 25 mL of ammonia water, then add 2.5 mL of tetraethoxysilane and stir to react for 1.5 h. After centrifugation at 7500 rpm, wash the precipitate with ethanol and deionized water, dry it in vacuo at 65 ° C for 22 h, transfer it to a muffle furnace, pass oxygen, heat it to 425 ° C and calcine it for 3.5 h to obtain a coated zirconium oxide carrier.

[0037] Step 5. Disperse 17.5 g of the coated zirconia carrier in 125 mL of anhydrous ethanol in a reactor, add 40 mL of 60 wt% ammonia water and stir vigorously for 40 min, then add 3.5 g of dodecyltriethoxysilane to the reactor, heat to 75 ° C and react for 6.5 h. After centrifugation, wash the precipitate with anhydrous ethanol and vacuum dry at 65 ° C for 13 h to obtain a hydrophobic coated zirconia carrier.

[0038] Step six: homogenize and mix the platinum catalyst and the inhibitor with 30 times their mass of polydimethylsiloxane respectively at a rotation speed of 1750 rpm using a planetary mixer, with each mixing time of 4 minutes to obtain a platinum catalyst dilution and an inhibitor dilution. Use a planetary mixer to homogenize and mix the remaining polydimethylsiloxane and the catalyst solution with the platinum catalyst solution and the inhibitor solution successively, with a mixing time of 4 minutes. Then, add the hydrophobic coated zirconia carrier three times, with each mixing time of 1.5 minutes, and then add the dimethylsiloxane copolymer terminated with methyl hydrogen siloxane and mix for 1.5 minutes to obtain a waterproof and high temperature resistant organic silicone adhesive.

[0039] Step seven: apply waterproof and high temperature resistant organic silicone adhesive on one side of the polyimide film to obtain an adhesive layer. The coating thickness of the adhesive layer is 45 μm, and the thickness of the polyimide film is 30 μm. A release film is attached to the lower surface of the adhesive layer. The release film is a fluoroplastic release film with a thickness of 60 μm to obtain a high temperature resistant splicing tape.

[0040] Embodiment 3: A high temperature resistant splicing tape, comprising, from top to bottom, a polyimide film, an adhesive layer and a release film, wherein the adhesive layer is coated with a waterproof and high temperature resistant organic silicone adhesive, and the waterproof and high temperature resistant organic silicone adhesive comprises the following components: 250 g polydimethylsiloxane, 0.1 g platinum catalyst, 0.01 g inhibitor, 20 g hydrophobically coated zirconium oxide support and 10 g cross-linking agent.

[0041] In this embodiment, the platinum catalyst is chloroplatinic acid / divinyltetramethyldisiloxane complex.

[0042] A production process of a high temperature resistant splicing tape comprises the following steps: Step 1: In a reaction kettle, 30 g of zirconium oxychloride octahydrate and 45 g of 2-aminoterephthalic acid are ultrasonically dispersed in a mixed solution of equal volumes of 1000 mL of formic acid and N,N-dimethylformamide, and the temperature is raised to 130°C for reaction for 48 hours. After cooling, the mixture is centrifuged at 8000 rpm for 5 minutes, and the precipitate is washed with N,N-dimethylformamide and ethanol respectively, and vacuum dried at 80°C for 12 hours to obtain a zirconium-based carrier.

[0043] A zirconium-based porous carrier with amino groups on its surface was hydrothermally synthesized using 2-aminoterephthalic acid as a ligand.

[0044] Step 2: In a reactor, add 20 g of L-histidine to 300 mL of deionized water, heat and stir to dissolve the L-histidine, add 20 g of the zirconium-based carrier activated at 130°C for 3 hours to the reactor, heat the reactor to 90°C and react for 12 hours, centrifuge at 8000 rpm after cooling, wash the precipitate with deionized water, and vacuum dry at 80°C for 12 hours to obtain a modified zirconium-based carrier.

[0045] By utilizing the grafting reaction between L-histidine and amino groups and the electrostatic interaction between L-histidine and zirconium elements, L-histidine is grafted into the porous structure on the surface of the zirconium-based carrier, so that the surface of the zirconium-based carrier contains carboxyl groups.

[0046] Step 3: In a reactor, disperse 20 g of the modified zirconium-based carrier in 300 mL of a 5 wt% zinc nitrate methanol solution and stir to react for 36 h. Then, add 30 mL of deionized water and 15 g of hexamethylenetetramine to the reactor, stir evenly, heat to 130 ° C, react for 8 h, cool, centrifuge at 8000 rpm to obtain a bottom precipitate, wash the precipitate with methanol, and vacuum dry at 80 ° C for 12 h to obtain a zinc oxide / zirconium-based carrier.

[0047] The carboxyl groups on the surface of the zirconium-based carrier are used to uniformly graft zinc ions in the zinc nitrate methanol solution into the porous structure on the surface of the zirconium-based carrier. Then, in the presence of water and hexamethylenetetramine, a solvothermal method is used in a water-alcohol solvent system to in-situ generate zinc oxide from the zinc ions on the surface of the zirconium-based carrier. The zinc oxide is loaded on the zirconium-based carrier to form a zinc oxide / zirconium-based carrier with uniform bonding and high bonding strength.

[0048] Step 4: In a reactor, ultrasonically disperse 20 g of zinc oxide / zirconium-based carrier in 600 mL of 90 wt% ethanol solution, add 30 mL of ammonia water, then add 3 mL of tetraethoxysilane and stir to react for 2 h. After centrifugation at 8000 rpm, wash the precipitate with ethanol and deionized water, dry it in vacuo at 70 ° C for 24 h, transfer it to a muffle furnace, pass oxygen, heat it to 450 ° C and calcine it for 4 h to obtain a coated zirconium oxide carrier.

[0049] The zinc oxide / zirconium-based carrier is hydrolyzed in tetraethoxysilane under the catalytic action of ammonia water, and silicon dioxide is in situ generated on the surface of the zinc oxide / zirconium-based carrier. Then, under high-temperature oxygen calcination conditions, the organic matter in the zirconium-based carrier is reacted with oxygen to generate carbon dioxide for removal, and the zirconium element is oxidized to generate zirconium oxide, so that the zirconium oxide, zinc oxide and silicon dioxide are firmly combined under the action of calcination.

[0050] Step 5. Disperse 20 g of the coated zirconia carrier in 150 mL of anhydrous ethanol in a reactor, add 50 mL of 60 wt% ammonia water and stir vigorously for 50 min, then add 4 g of dodecyltriethoxysilane to the reactor, heat to 80 ° C and react for 7 h. After centrifugation, wash the precipitate with anhydrous ethanol and vacuum dry at 70 ° C for 14 h to obtain a hydrophobic coated zirconia carrier.

[0051] Dodecyltriethoxysilane is used to modify the silicon dioxide on the surface of the coated zirconium oxide carrier, so that the silicon dioxide produces a hydrophobic effect and enhances the waterproof ability of the hydrophobic coated zirconium oxide carrier.

[0052] Step six: homogenize and mix the platinum catalyst and the inhibitor with 30 times their mass of polydimethylsiloxane respectively at a rotation speed of 1800 rpm using a planetary mixer, and mix each time for 5 minutes to obtain a platinum catalyst dilution and an inhibitor dilution. Use a planetary mixer to homogenize and mix the remaining polydimethylsiloxane and the catalyst solution with the platinum catalyst solution and the inhibitor solution successively for 5 minutes, and then add the hydrophobic coated zirconia carrier three times, each mixing time for 2 minutes, and then add the methyl hydrogen siloxane-terminated dimethylsiloxane copolymer and mix for 2 minutes to obtain a waterproof and high temperature resistant organic silicone adhesive.

[0053] The hydrophobic silica in the hydrophobic coated zirconia carrier can improve the hydrophobic ability of the surface of the organic silicone adhesive and enhance the moisture resistance of the organic silicone adhesive. At the same time, silica as a filler can also be used as a heat-resistant filler to improve the high temperature resistance of the organic silicone adhesive, while zirconium oxide can be used as a volume compensator to improve the density of the organic silicone adhesive at high temperatures. Zinc oxide can be used as a curing agent to improve the curing strength and cross-linking density of the organic silicone adhesive and reduce the intrusion of water molecules, thereby improving the mechanical properties and temperature and humidity resistance of the organic silicone adhesive.

[0054] Step seven: apply waterproof and high temperature resistant organic silicone adhesive on one side of the polyimide film to obtain an adhesive layer. The adhesive layer coating thickness is 50 μm, and the thickness of the polyimide film is 35 μm. A release film is attached to the lower surface of the adhesive layer. The release film is a fluoroplastic release film with a thickness of 75 μm to obtain a high temperature resistant splicing tape.

[0055] Comparative Example 1: The difference from Example 1 is that zirconium oxide is used to replace the modified zirconium oxide carrier.

[0056] Comparative Example 2: The difference from Example 1 is that the hydrophobic coated zirconia carrier is replaced by a coated zirconia carrier.

[0057] Comparative Example 3: The difference from Example 1 is that, in step 4, 15 g of zinc oxide / zirconium-based carrier is ultrasonically dispersed in 500 mL of 90 wt% ethanol solution in a reactor, 20 mL of ammonia water is added, and then 2 mL of tetraethoxysilane is added and stirred for 1 hour. After centrifugation at 7000 rpm, the precipitate is washed with ethanol and deionized water, and vacuum dried at 60°C for 20 hours to obtain a coated zirconium oxide carrier.

[0058] The crosslinking agent in the examples of the present invention and the comparative examples is a dimethylsiloxane copolymer terminated with methylhydrogensiloxane.

[0059] The reagents used in the examples and comparative examples of the present invention are all conventional reagents known to those skilled in the art.

[0060] The performance tests were conducted on the high temperature resistant splicing tapes prepared in Examples 1 to 3 and Comparative Examples 1 to 3. The spliced ​​articles were aluminum alloys. The tensile strength was tested at 85°C, 85°C / 85%RH, and 200°C, respectively. The tensile strength of the high temperature resistant splicing tape was tested when the elongated deformation reached 10%. The results are shown in Table 1: Table 1

[0061] It can be seen from Table 1 that the high temperature resistant splicing tape prepared by the present invention has good tensile strength at 85°C and 200°C when splicing objects, and has good splicing performance. Moreover, at a humidity of 85% / RH, the tensile strength only slightly decreases, indicating that the high temperature resistant splicing tape prepared by the present invention can still maintain good splicing ability under a high humidity environment; in Comparative Example 1, since zirconium oxide is directly grafted with zinc ions, there are fewer grafting sites between zirconium oxide and L-histidine, and the zinc oxide content in the obtained zinc oxide zirconium-based carrier is low, and the performance of the obtained high temperature resistant splicing tape is poor; in Comparative Example 2, since The silica was not hydrophobically modified, and the waterproof performance of the obtained high-temperature resistant splicing tape was weak, and the dispersibility of the coated zirconia carrier in organic solvents was worse than that of the hydrophobic coated zirconia carrier, and the obtained high-temperature resistant splicing tape had poor performance and poor moisture resistance; in Comparative Example 3, since the coated zirconia carrier was not oxygen-calcined, the ligands in the zirconium-based carrier were not removed, the volume of the hydrophobic coated zirconia carrier was increased, and the high-temperature resistance of zirconium oxide was not improved. The bonding force between the components of the uncalcined hydrophobic coated zirconia carrier was low, and the obtained high-temperature resistant splicing tape had weak high-temperature resistance.

[0062] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device.

[0063] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A high temperature resistant splicing tape, comprising, from top to bottom, a polyimide film, an adhesive layer and a release film, characterized in that: The adhesive layer is obtained by coating with a waterproof and high temperature resistant organic silicone adhesive, and the waterproof and high temperature resistant organic silicone adhesive comprises the following components in parts by mass: 200-250 parts of polydimethylsiloxane, 0.05-0.1 parts of platinum catalyst, 0.005-0.01 parts of inhibitor, 10-20 parts of hydrophobically coated zirconium oxide carrier and 5-10 parts of cross-linking agent; The inhibitor is 1-ethynyl-1-cyclohexanol; The crosslinking agent is a methylhydrogensiloxane-terminated dimethylsiloxane copolymer.

2. The production process of a high temperature resistant splicing tape according to claim 1, characterized in that: The steps include: Step 1: homogenize and mix the platinum catalyst and the inhibitor with polydimethylsiloxane of 30 times their mass respectively at a rotation speed of 1500-1800rpm with a planetary mixer for 3-5min to obtain a platinum catalyst dilution and an inhibitor dilution, and homogenize and mix the remaining polydimethylsiloxane and the catalyst solution with the platinum catalyst solution and the inhibitor solution successively with a planetary mixer for 3-5min each time, and then add the hydrophobic coated zirconium oxide carrier three times, each mixing time is 1-2min, and finally add the cross-linking agent and mix for 1-2min to obtain a waterproof and high temperature resistant organic silicone adhesive; Step 2: Apply waterproof and high temperature resistant organic silicone adhesive on one side of the polyimide film to obtain an adhesive layer, the adhesive layer coating thickness is 40-50 μm, the thickness of the polyimide film is 25-35 μm, and a release film is attached to the lower surface of the adhesive layer. The release film is a fluoroplastic release film with a thickness of 50-75 μm to obtain a high temperature resistant splicing tape.

3. The production process of a high temperature resistant splicing tape according to claim 2, characterized in that: The hydrophobic coated zirconia carrier is prepared by the following steps: In a reaction kettle, the coated zirconia carrier is dispersed in anhydrous ethanol, 60wt% ammonia water is added and stirred vigorously for 30-50min, then dodecyltriethoxysilane is added to the reaction kettle, the temperature is raised to 70-80°C and the reaction is carried out for 6-7h, the precipitate is washed after centrifugation, and vacuum dried to obtain a hydrophobic coated zirconia carrier.

4. The production process of a high temperature resistant splicing tape according to claim 3, characterized in that: The usage ratio of the coated zirconium oxide carrier, anhydrous ethanol, ammonia water and dodecyltriethoxysilane is 15-20g: 100-150mL: 30-50mL: 3-4g.

5. The production process of a high temperature resistant splicing tape according to claim 4, characterized in that: The coated zirconium oxide carrier is prepared by the following steps: In a reaction kettle, the zinc oxide / zirconium-based carrier is ultrasonically dispersed in a 90wt% ethanol solution, ammonia water is added, and then tetraethoxysilane is added and stirred for reaction for 1-2 hours. The precipitate is washed after centrifugation, vacuum dried, and transferred to a muffle furnace and heated to 400-450°C and calcined for 3-4 hours by passing oxygen to obtain a coated zirconium oxide carrier.

6. The production process of a high temperature resistant splicing tape according to claim 5, characterized in that: The dosage ratio of the zinc oxide / zirconium-based carrier, ethanol solution, ammonia water and tetraethoxysilane is 15-20 g: 500-600 mL: 20-30 mL: 2-3 mL.

7. The production process of a high temperature resistant splicing tape according to claim 6, characterized in that: The zinc oxide / zirconium-based carrier is prepared by the following steps: The modified zirconium-based carrier is dispersed in a 5wt% zinc nitrate methanol solution in a reactor and stirred for 24-36 hours. Then, deionized water and hexamethylenetetramine are added to the reactor, stirred evenly, heated to 120-130°C and reacted for 6-8 hours. After cooling, the precipitate is washed by centrifugation and vacuum dried to obtain a zinc oxide / zirconium-based carrier.

8. The production process of a high temperature resistant splicing tape according to claim 7, characterized in that: The usage ratio of the modified zirconium-based carrier, zinc nitrate methanol solution, deionized water and hexamethylenetetramine is 15-20 g: 200-300 mL: 20-30 mL: 10-15 g.

9. The production process of a high temperature resistant splicing tape according to claim 8, characterized in that: The modified zirconium-based carrier is prepared by the following steps: S1. In a reaction kettle, zirconium oxychloride octahydrate and 2-aminoterephthalic acid are ultrasonically dispersed in a mixed solution of formic acid and N,N-dimethylformamide in equal volumes, the temperature is raised to 100-130° C. and reacted for 40-48 hours. After cooling, centrifugation is performed, the precipitate is washed, and vacuum drying is performed to obtain a zirconium-based carrier; S2. In a reactor, heat and stir L-histidine in deionized water to dissolve the L-histidine, add the zirconium-based carrier activated at 120-130°C for 2-3 hours into the reactor, heat the reactor to 80-90°C for 10-12 hours, cool and centrifuge, wash the precipitate, and vacuum dry to obtain a modified zirconium-based carrier.

10. The production process of a high temperature resistant splicing tape according to claim 9, characterized in that: The usage ratio of zirconium oxychloride octahydrate, 2-aminoterephthalic acid and the mixed solution in S1 is 25-30g:40-45g:800-1000mL; the usage ratio of L-histidine, deionized water and zirconium-based carrier in S2 is 10-20g:200-300mL:15-20g.

Citation Information

Patent Citations

  • Modified acrylic adhesive tape

    CN116120848A

  • High-temperature-resistant adhesive tape

    CN117004336A